RACE, MILIEU, AND MOMENT IN “TITANIC” BY JAMES CAMERON: HISTORICAL APPROACH - Icha Sartika; Tomi Arianto (eScience Humanity Journal, 2021)
Literary criticism is defined as a science and try to investigate literary work with analyse and comparison. The purpose of this study is to get some information and to identify the race milieu and moment in literary work. Outlined Hipollyte Taine perspective in three concepts, namely (1) race, (2) Milieu, and (3) Moment. This phenomenon occurs in Titanic film by James Cameron. The researcher using Qualitative descriptive methods to analyse race, milieu and moment in Titanic film by James Cameron. The data collected by recording the data. Data analysed using Hippolyte Taine and Guerin theory for historical biographical approach. The result of analysis found that the disparity in the status of ship passengers for the poorer and upper classes is depicted in James Cameron's film Titanic as evidence of social class inequality. Because of his act of obtaining an award despite being in the lower class, Jack, as a class representative, does not have the right to be considered a person at the bottom. Mileu pits the position of social class against the community, which is backed up by the class division. Meanwhile, Moment is viewed through the lens of a social class that exists between the bourgeoisie and the proletariat, as evidenced by the numerous forms of discrimination discovered.